THE MEDIATING ROLE OF JOB SATISFACTION IN THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND TRANSFORMATIONAL LEADERSHIP ON THE JOB PERFORMANCE - Levira Luciana leonata; Agustiono (RADJA PUBLIKA, 2025)
Nowadays, the business competition in Indonesia is becoming very hard, especially in the distribution and food beverage sector. Many companies struggle with human resource problems. One major issue is high turnover, meaning many employees resign from their jobs frequently. This study investigates PT. Kapitan Prima Mandiri, a company currently facing this specific problem. The management aims to understand how to improve employee performance and retention. This research focuses on two main factors: the leadership style of the supervisor (Transformational Leadership) and the emotional skills of the employees (Emotional Intelligence). The objective is to determine if these factors improve Job Performance and to check if Job Satisfaction acts as a